FAKTOR-FAKTOR YANG MEMENGARUHI NILAI TUKAR PETANI DI 10 PROVINSI DENGAN PERAN SEKTOR PERTANIAN TERTINGGI 2010-2020 - Reynaldi Galuh Mulyana; Istiqomah Istiqomah; Pahrul Fauzi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
In terms of GDP, the agriculture sector is the second biggest driver of the expansion of the national economy in 2019–2020. Despite the agriculture sector's significant contribution, it cannot be claimed that farmers' conditions are prosperous. A method used to gauge the degree of farmer welfare is the Farmer Exchange Rate (FER). The study's objective is to examine how labor productivity, rice productivity, and output of rice affect FER in Indonesia's ten provinces with the largest sector contributions. One sort of data that is used with the panel data multiple regression analysis approach is called secondary data. The findings of this study clarify that, in ten Indonesian provinces that are the subject of research from 2010 to 2020, While rice yield and productivity do not significantly affect FER, labour productivity does. The findings of this study offer recommendations for additional measures that the government should implement to reduce production costs.